Structural investigations of superconducting multilayers consisting of semiconducting materials - Erenburg, A. I.; Fogel, N. Ya.; Bomze, Yu. V.; Sipatov, A. Yu.; Fedorenko, A. I.; Langer, V.; Norell, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
There are rather exotic semiconducting superlattices (SL) consisting of monochalcogenides of Pb, Sn and rare-earth metals which exhibit superconductivity at temperature as high as 6 K. Here we report the results of precision x-ray diffractometry and TEM investigations as well as Auger spectroscopy data obtained on some of the epitaxially grown superconducting semiconducting SLs. It is established that essential features of the SL structure determining the appearance of superconductivity are the perfect single-crystallinity of the samples and the presence of continuous dense grids of misfit dislocations on the interfaces between two semiconductors. The segregation of free Pb which was observed in some cases does not correlate, according to experimental data, with the appearance of superconductivity.